PENINGKATAN KESADARAN MELALUI EDUKASI PENCEGAHAN KEKERASAN DALAM RUMAH TANGGA DI KELURAHAN BATANG ARAU KOTA PADANG - Anggela Pradiva Putri; Isti Aryani; Novira Ramadani; Firmanita Firmanita; Rahmi Syahriza (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2024)
Domestic Violence is a complex and pervasive social issue that occurs worldwide. Domestic violence is gender-based violence that occurs in the personal sphere. The prevalence of domestic violence is very high globally, with approximately 1 in 3 women experiencing sexual or physical violence from their partners at some point in their lives. The aim of this activity is to raise public awareness of domestic violence, increase knowledge, promote information dissemination, empower women, and engage in action plans for the prevention of domestic violence. It is hoped that this will help prevent the occurrence of violence, which can reduce the quality of life and health of individuals and their surrounding environment.The methods used include lectures and Q&A discussions between the speakers and 25 participants of the education session. The implementation stages of the activity begin with a pre-test, followed by the presentation of material related to domestic violence, its causes, various forms, its impact on various aspects, and its prevention. Finally, a post-test is conducted. The results obtained from the paired sample test show a p-value of 0.000, indicating a probability above the significant level (0.000 < 0.05). The conclusion is that there is an increase in the participants' knowledge about the prevention of domestic violence before and after the education session. It is hoped that the community can prevent domestic violence and support the creation of a violence-free environment.